Method for manufacturing electrode, electrode, and battery

JP2025025609AInactive Publication Date: 2025-02-21TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023130507
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0007】 本開示の一実施形態によれば、電子伝導性に優れる電極の製造方法、電子伝導性に優れる電極、及び電子伝導性に優れる電極を備える電池が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025609000001
    Figure 2025025609000001
Patent Text Reader

Abstract

To provide a method for manufacturing an electrode with an excellent electron conductivity, an electrode with an excellent electronic conductivity, and a battery having an electrode with an excellent electron conductivity.SOLUTION: The method for manufacturing an electrode includes the steps of: mixing active material particles, a conductive material, and an adhesive and fixing the conductive material to at least a part of the surface of the active material particles; and mixing the active material particles with the conductive material fixed by the additive and polytetrafluoroethylene, thereby obtaining a mixture; and fibrillating the polytetrafluoroethylene in the mixture.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing an electrode, an electrode, and a battery. [Background technology]

[0002] 2. Description of the Related Art Batteries such as lithium ion secondary batteries use electrodes in which active material particles are fixed to the surface of a current collector such as a metal foil with a binder. Known methods for manufacturing electrodes include a method (also called a wet method) in which a composition made by mixing active material particles and a binder with a solvent is applied to the surface of a current collector, and a method (also called a dry method) in which active material particles are fixed to a current collector with a binder without using a solvent.

[0003] As a method for manufacturing an electrode by a dry method, a method has been proposed in which a resin that has the property of being fibrillated when a shear force is applied is used as a binder. For example, Patent Document 1 describes a method in which PTFE in a mixture containing active material particles and polytetrafluoroethylene (PTFE) is fibrillated to produce an electrode film, and then this electrode film is integrated with a current collector to manufacture an electrode. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2022-3694 A Summary of the Invention [Problem to be solved by the invention]

[0005] There is room for improvement in electronic conductivity of the electrode obtained by the method described in Patent Document 1. An object of the present disclosure is to provide a method for producing an electrode having excellent electronic conductivity, an electrode having excellent electronic conductivity, and a battery including an electrode having excellent electronic conductivity. [Means for solving the problem]

[0006] Means for solving the above problems include the following embodiments. <1> a step of kneading active material particles, a conductive material, and an adhesive to fix the conductive material to at least a portion of the surface of the active material particles; A step of mixing the active material particles having the conductive material fixed thereto with an adhesive with polytetrafluoroethylene to obtain a mixture; and converting the polytetrafluoroethylene in the mixture into fibers. <2> The coverage of the active material particles with the conductive material is 10% or more. <1> A method for producing the electrode according to claim 1. <3> A current collector and an electrode layer are included. The electrode layer includes active material particles having a conductive material fixed to at least a portion of a surface thereof with an adhesive, and fibrous polytetrafluoroethylene. <4> The coverage of the active material particles with the conductive material is 10% or more. <3> The electrode according to claim 1. <5> <3> or <4> A battery comprising the electrode according to claim 1. Effect of the Invention

[0007] According to one embodiment of the present disclosure, there are provided a method for producing an electrode with excellent electronic conductivity, an electrode with excellent electronic conductivity, and a battery including an electrode with excellent electronic conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of multiple substances, unless otherwise specified.

[0009] <Electrode manufacturing method> The method for producing an electrode according to the present disclosure includes: a step of kneading active material particles, a conductive material, and an adhesive to fix the conductive material to at least a portion of the surface of the active material particles; A step of mixing the active material particles to which the conductive material is fixed with an adhesive with PTFE to obtain a mixture; and forming PTFE in the mixture into fiber.

[0010] The electrode produced by the method of the present disclosure exhibits superior electronic conductivity compared to an electrode formed from a mixture obtained by simultaneously mixing active material particles, a conductive material, and PTFE, for the following reasons, for example. If PTFE is made into fiber without the conductive material being fixed to the active material particles with an adhesive, the conductive material will be trapped within the fibrous PTFE, and the contact area between the active material particles and the conductive material will not be sufficient. In contrast, in the method of the present disclosure, the conductive material is fixed to the surface of the active material particles with an adhesive before the PTFE is fiberized. Therefore, even after the PTFE is fiberized, the conductive material is not easily taken into the fibrous PTFE, and the contact area between the active material particles and the conductive material is sufficiently secured. As a result, good electronic conductivity is achieved. Furthermore, in the method of the present disclosure, the conductive material is fixed to the active material particles with an adhesive, which makes it more difficult for the conductive material to separate from the active material particles than when the conductive material is fixed to the active material particles without the use of an adhesive, and makes it easier to ensure a sufficient contact area between the conductive material and the active material particles.

[0011] According to the method of the present disclosure, an electrode can be produced without using a solvent, which is advantageous in terms of reducing the production cost of the electrode and reducing the impact on the environment and living organisms.

[0012] Hereinafter, the process of kneading the active material particles, the conductive material, and the adhesive to fix the conductive material to at least a portion of the surface of the active material particles will be referred to as "process 1," the process of mixing the active material particles to which the conductive material is fixed with PTFE to obtain a mixture will be referred to as "process 2," and the process of fiberizing the PTFE in the mixture will be referred to as "process 3."

[0013] (Process 1) In step 1, active material particles, a conductive material, and an adhesive are kneaded to fix the conductive material to at least a portion of the surface of the active material particles. The type of active material particles used in this step is not particularly limited and can be selected from materials commonly used in the manufacture of electrodes. The active material particles may be positive electrode active material particles or negative electrode active material particles.

[0014] The positive electrode active material may be a lithium transition metal composite oxide. Examples of the transition metal include Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, and W. Among them, a lithium transition metal composite oxide containing at least one selected from Ni, Co, and Mn is preferable, and a lithium transition metal composite oxide (NCM, nickel cobalt manganese oxide) containing Ni, Co, and Mn is more preferable. Specific examples of lithium transition metal composite oxides include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their composite oxides (LiCo x Ni y Mn z O2, x+y+z=1), and a double oxide containing an additive element M' (LiCo a Ni b Mn c M' dO2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel-type lithium manganese oxide (LiMn2O4), olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), etc. The positive electrode active material used in the production of the electrode may be one type alone or two or more types. The volume average particle size of the positive electrode active material particles is not particularly limited and can be selected, for example, from the range of 5 μm to 30 μm.

[0015] Specific examples of the negative electrode active material include carbon materials such as graphite, soft carbon, and hard carbon, and silicon. The negative electrode active material used in the production of the electrode may be one type alone or two or more types. The volume average particle size of the negative electrode active material particles is not particularly limited and can be selected, for example, from the range of 5 μm to 30 μm.

[0016] In the present disclosure, the volume average particle size of particles is the value (D50) at which the cumulative amount from the small diameter side reaches 50% in the volume-based particle size distribution measured by a laser diffraction / scattering method.

[0017] The type of conductive material used in this step is not particularly limited, and can be selected from materials commonly used in the manufacture of electrodes. Specific examples of the conductive material include carbon materials such as carbon black (acetylene black, thermal black, furnace black, etc.), carbon nanotubes, and graphite. The conductive material used in the production of the electrode may be one type alone or two or more types.

[0018] The type of adhesive used in this step is not particularly limited, and can be selected from materials commonly used in the manufacture of batteries. Specific examples of adhesives include polyvinylidene fluoride, polyethylene, polypropylene, polyethylene terephthalate, cellulose, nitrocellulose, carboxymethyl cellulose, polyethylene oxide, polyepichlorohydrin, polyacrylonitrile, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), polyacrylate, and polymethacrylate. The adhesive used in this step may be of one type alone or of two or more types. From the viewpoints of adhesive strength, affinity with PTFE, resistance to electrolyte, etc., polyvinylidene fluoride (PVdF) is preferred as the adhesive.

[0019] From the viewpoint of obtaining a sufficient effect of improving electronic conductivity, the coverage of the surface of the active material particles with the conductive material is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more. The coverage of the surface of the active material particles with the conductive material may be 80% or less, 70% or less, 60% or less, or 50% or less.

[0020] The coverage of the surfaces of the active material particles with the conductive material is measured by an image analysis method. As an image analysis method, there is a method of performing C mapping by EDX (energy dispersive X-ray spectroscopy). Specifically, active material particles to which a conductive material is fixed with an adhesive are observed by SEM (scanning electron microscope), and C mapping is performed by EDX. Regions X corresponding to active material particles and regions Y within region X where a conductive material (C) exists are binarized, and the coverage is calculated by the following formula. Coverage rate (%) = (Y area / X area) x 100

[0021] In this step, the method for kneading the active material particles, the conductive material, and the adhesive is not particularly limited as long as it is possible to fix the conductive material to the surfaces of the active material particles, and can be carried out using known means. The amount of the conductive material relative to 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 parts by mass to 10 parts by mass, or 1 part by mass to 5 parts by mass. The amount of adhesive per 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 parts by mass to 10 parts by mass, or 1 part by mass to 5 parts by mass.

[0022] (Process 2) In step 2, the active material particles to which the conductive material is fixed with the adhesive and PTFE are mixed to obtain a mixture. The mixing method is not particularly limited, and can be carried out by using a known means. The amount of PTFE relative to 100 parts by mass of the active material particles in the mixture can be selected, for example, from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass.

[0023] The PTFE mixed with the active material in step 2 may be in particulate form. The mixture obtained in step 2 may not contain a solvent. In step 2, at least a portion of the PTFE may be fibrous, and a granule may be produced in which the active material particles are bound by the fibrous PTFE.

[0024] The mixture of PTFE and active material particles to which the conductive material is fixed with an adhesive may contain a binder other than PTFE, which may be selected from the adhesives described above, for example. When the mixture contains a binder other than PTFE, the content thereof may be 20 parts by mass or less, 10 parts by mass or less, or 5% by mass or less relative to 100 parts by mass of PTFE.

[0025] (Step 3) In step 3, the PTFE in the mixture obtained in step 2 is fiberized. The method for converting PTFE into fibers is not particularly limited, and can be carried out by using known means. From the viewpoint of workability when integrating the mixture after fiberizing PEFE with the current collector, it is preferable to fiberize PTFE and mold the mixture into a sheet in step 3. As a method for converting PTFE into fibers and forming the mixture into a sheet, for example, a rolling treatment using a roll press machine can be mentioned.

[0026] The thickness of the molded product obtained by forming the mixture into a sheet is not particularly limited and can be adjusted according to the desired thickness of the electrode layer. For example, the thickness of the molded product can be selected in the range of 10 μm to 200 μm.

[0027] The mixture obtained after fiberizing PTFE in step 3, preferably a sheet-like molded product, is integrated with a current collector to form an electrode. The method for integrating the mixture obtained by fiberizing PTFE with the current collector is not particularly limited, and can be carried out by using a known means. For example, the mixture and the current collector may be pressure-bonded using a roll press, a plate press, or the like. The material of the current collector is not particularly limited, and can be selected from known materials such as aluminum, copper, nickel, titanium, and stainless steel.

[0028] <Electrode> The electrode of the present disclosure comprises: A current collector and an electrode layer are included. The electrode layer is an electrode including active material particles having a conductive material fixed to at least a portion of the surface thereof with an adhesive, and fibrous PTFE (PTFE fibers).

[0029] The electrode of the present disclosure exhibits superior electronic conductivity compared to an electrode in which a conductive material is not fixed to the surface of the active material particles with an adhesive.

[0030] The details and preferred aspects of the electrode and each material contained in the electrode of the present disclosure are the same as the details and preferred aspects of the electrode manufactured by the above-mentioned electrode manufacturing method and each material used therein.

[0031] The electrode of the present disclosure may further include a member other than the current collector and the electrode layer including the active material particles and the PTFE fibers. For example, the electrode of the present disclosure may further include an electrode layer that does not include the PTFE fibers.

[0032] <Battery> The battery of the present disclosure includes the electrode of the present disclosure described above. Batteries of the present disclosure include an electrode of the present disclosure as at least one of a positive electrode or a negative electrode, and in some embodiments, include an electrode of the present disclosure as a positive electrode.

[0033] The type of battery disclosed herein is not particularly limited, and can be selected from batteries such as lithium ion secondary batteries (including liquid batteries and all-solid-state batteries), lead acid batteries, nickel-metal hydride batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, cobalt titanium lithium secondary batteries, and sodium ion secondary batteries. EXAMPLES

[0034] The present disclosure will be described in more detail below with reference to examples, but the invention of the present disclosure is not limited to these examples.

[0035] <Example: Preparation of Positive Electrode> The materials listed below were put into an MP mixer (Nippon Coke & Engineering Co., Ltd.), and a composite treatment was carried out at 10,000 rpm for 10 minutes to fix the conductive material to the surface of the active material particles with an adhesive. Positive electrode active material particles: NCM (volume average particle size: 10 μm, 96.6 parts by mass) Conductive material: Acetylene black (1.5 parts by mass) Adhesive: PVdF (0.5 parts by weight)

[0036] After the composite treatment, PTFE (1.4 parts by mass) was further added to the MP mixer and mixed at 300 rpm for 180 seconds, followed by further mixing at 5000 rpm for 500 seconds to form granules in which the active material particles were bound by the fibrous PTFE.

[0037] The mixture containing the granules was rolled (linear pressure: 0.4 t / cm) using a roll press machine to convert the PTFE into fibers and form them into a sheet (thickness: 120 μm). The sheet-like molded body and aluminum foil (thickness: 12 μm) serving as a current collector were bonded together using a roll press (linear pressure: 4 t / cm, 160° C.).

[0038] <Comparative Example: Preparation of Positive Electrode> The following materials were put into an MP mixer (Nippon Coke Industries Co., Ltd.) and mixed at 300 rpm for 180 seconds. Then, the materials were further mixed at 5000 rpm for 500 seconds to form a granule in which the active material particles were bound by the fiberized PTFE. The amount of the binder was set so that the total volume was equal to the total volume of the binder used in Example 1. Positive electrode active material particles: NCM (volume average particle size: 10 μm, 96.5 parts by mass) Conductive material: Acetylene black (1.5 parts by mass) Binder: PTFE (2.0 parts by mass)

[0039] The mixture containing the granules was rolled (linear pressure: 0.4 t / cm) using a roll press machine to convert the PTFE into fibers and form them into a sheet (thickness: 10 μm). The sheet-like molded body and aluminum foil (thickness: 12 μm) serving as a current collector were bonded together using a roll press (linear pressure: 4 t / cm, 160° C.).

[0040] <Evaluation of coverage> The cross sections of the positive electrodes prepared in the examples and comparative examples were observed with an SEM, and C mapping was performed with an EDX attached to the SEM to calculate the coverage of the active material particles with the conductive material. The results are shown in Table 1.

[0041] <Evaluation of electronic conductivity> As indicators of the electronic conductivity of the positive electrodes prepared in the examples and comparative examples, the resistance inside the electrode layer (electrode layer resistance) and the resistance at the interface between the electrode layer and the current collector (interface resistance) were measured using an electrode resistance measurement system RM2610 (HIOKI EE Corporation). The results are shown in Table 1.

[0042] A small cell for measuring IV resistance was prepared using the positive electrodes prepared in the Examples and Comparative Examples and the negative electrodes prepared by the following method. The IV resistance was calculated by the following method using this small cell. The results are shown in Table 1. Measurement method: Discharge for 10 seconds at a current I of 0.3C, and measure the voltage drop ΔV over that time. Calculate the IV resistance from the relationship between current I and ΔV.

[0043] (Preparation of negative electrode) A paste containing graphite (volume average particle size: 20 μm, 98 parts by mass) as a negative electrode active material and carboxymethyl cellulose (0.4 parts by mass) and SBR (1.6 parts by mass) as binders was applied onto copper foil (thickness: 8 μm) as a current collector to prepare a negative electrode.

[0044] [Table 1]

[0045] As shown in Table 1, the positive electrode of the embodiment made from PTFE and active material particles having a conductive material fixed to the surface with an adhesive has a higher coverage rate of the active material with the conductive material than the positive electrode of the comparative example made from PTFE and active material particles not having a conductive material fixed to the surface with an adhesive. Furthermore, the positive electrode of the embodiment made from PTFE and active material particles having a conductive material fixed to the surface with an adhesive has lower electrode layer resistance, interface resistance, and IV resistance than the positive electrode of the comparative example made from PTFE and active material particles not having a conductive material fixed to the surface with an adhesive. The above results suggest that fixing the conductive material to the surface of the active material particles with an adhesive increases the coverage of the active material particles with the conductive material, further contributing to improved electronic conductivity.

Claims

1. a step of kneading active material particles, a conductive material, and an adhesive to fix the conductive material to at least a portion of the surface of the active material particles; A step of mixing the active material particles having the conductive material fixed thereto with an adhesive with polytetrafluoroethylene to obtain a mixture; and converting the polytetrafluoroethylene in the mixture into fibers.

2. The method for producing an electrode according to claim 1 , wherein a coverage of the active material particles with the conductive material is 10% or more.

3. A current collector and an electrode layer are included. The electrode layer includes active material particles having a conductive material fixed to at least a portion of a surface thereof with an adhesive, and fibrous polytetrafluoroethylene.

4. The electrode according to claim 3 , wherein the coverage of the active material particles with the conductive material is 10% or more.

5. A battery comprising the electrode according to claim 3 or 4.

Citation Information

Patent Citations

  • Manufacturing method of positive electrode for lithium secondary battery, positive electrode for lithium secondary battery, and agglomerated material

    JP2015170550A

  • Composite particle, electrode, power storage device, method for producing composite particle, and method for producing electrode

    JP2022083160A

  • PTFE powder, method for producing electrode, and electrode

    WO2022024520A1

  • Electrode and method for producing electrode

    WO2022070542A1

  • Positive electrode active material for secondary battery, method for preparing same, free-standing film comprising same, dry positive electrode, and secondary battery comprising dry positive electrode

    WO2022114860A1